TEOLOGI KEBANGSAAN ISLAM PESANTREN: FORMULASI KONSEP TEORITIS DAN KONSTRUKSI PRAKTIK KEBANGSAAN MASYARAKAT PESANTREN - Muhammad Afan; Ach. Maimun; Hariyanto; Atiqur Rahman Binuri Ramadan; Moh. Ali Mahdi (STAI Nusantara Kota Banda Aceh, 2026)
This study examines the nationalist theology of pesantren (Islamic boarding schools) and its concrete manifestations in the social practices of the pesantren community. Classical pesantren literature has long embedded principles of nationalism (hubb al-wathan) within its theological and jurisprudential framework, yet a systematic formulation of this concept and its practical dimensions has not been comprehensively articulated. This study employs a library research approach combined with an ethnographic dimension, grounded in the theory of maqashid al-syariah and the concept of ukhuwah wathaniyah as developed by pesantren scholars, and enriched with reference to contemporary Scopus- and Sinta-indexed studies on pesantren nationalism. Two principal conclusions emerge. First, the theoretical framework of pesantren nationalism rests upon the theological foundation that love of homeland (hubb al-wathan) is an integral part of faith (iman), as affirmed by classical scholars. This manifests in the veneration of national symbols, the tradition of flag-raising ceremonies, and the cultivation of ukhuwah wathaniyah (national brotherhood) as a binding force of the nation. Second, the practical dimensions of pesantren nationalism encompass: the active honoring of the state through respect for its symbols and institutions; the practice of bela negara (national defense) as a religious obligation; contributions to national development in education, economy, and social welfare; and participation in resolving national problems through dialogue, deliberation, and moral-religious guidance. These findings confirm that pesantren is not merely a religious educational institution, but also a primary pillar of Indonesian nationalism.